Pengaruh Budaya Kerja terhadap Semangat dan Kegairahan Kerja Karyawan Kantor Pusat PT. Bank Lampung - Robbyadi Afitno (Business Perspective Journal, 2022)
Bank Lampung is a Bank owned by the Lampung Regional Government in the form of a Regional Company. The problems encountered are the influence of work culture on the enthusiasm and enthusiasm of employees at the Head Office of PT. Lampung Bank. The method used is library research and field research. The purpose of this study was to determine how the influence of work culture on the enthusiasm and enthusiasm of the employees of the Head Office of PT. Lampung Bank. The results showed that there was a positive influence between work culture on employee morale and enthusiasm for work of 0.9082. To test the effect, the t-test was used where the coefficient of tcount was compared with ttable, which turned out to be tcount > ttable. Based on the Coefficient of Determination formula, the magnitude of the influence of work culture on employee morale and enthusiasm is 90.82%. Thus, the hypothesis proposed that there is a positive influence between work culture on the enthusiasm and enthusiasm of the employees of the Head Office of PT. Bank Lampung accepted. Keyword : culture, work, passion, employees